QUANTITATIVE DETERMINATION OF AMOXICILLIN FROM FORMULATED DOSAGE FORM BY REVERSED PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY SEPARATION TECHNIQUE AND A NEW METHOD VALIDATION - Chandra, Raju (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main purpose of this study is to develop and method validation for the determination of active constituent amoxicillin from the formulated dosage form according to International Council for Harmonization Guidelines. Methods: To method validation a reversed phase high-performance liquid chromatography (liquid-liquid chromatography) technique in isocratic mode has applied. Results: The wavelength of the amoxicillin was identifying 273 nm with ultraviolet-visible spectrophotometer. The retention time (R ) of amoxicillin was identify 4.66 minutes at the flow rate of mobile phase 1.0 ml/minute. The correlation coefficient (R ) was calculated 0.99 with correlation range 5-100 Î¼g/ml. The limit of detection and limit of quantification values for amoxicillin were calculated 0.03 and 0.09 Âµg/ml, respectively. The recoveries for amoxicillin were calculated 96.80, 98.0 and 102.72%. 2 Conclusions: The developed method is suitable for assured the quality of amoxicillin from formulated dosage form. This method can be successfully used for a routine bases analysis in a quality control laboratory. Keywords: Reversed phase high-performance liquid chromatography, Amoxicillin, Dosage form. t